A theorem on the rate of convergence to the stable law - Mitalauskas, A. (Lithuanian Mathematical Journal, 1972)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: А. Миталаускас. Одна теорема о скорости сходимости к устойчивому закону A. Mitalauskas. Viena teorema apie konvergavimo į stabilų dėsnį greitį